Effectiveness of Complementary Therapy Decoction of Celery Leaves and Bay Leaves on Reducing Hypertension in Paku Alam Village: Efektivitas Terapi Komplementer Rebusan Daun Seledri Dan Daun Salam Terhadap Penurunan Hipertensi Di Desa Paku Alam - Devina, Trisna; Muhammad Riduansyah; Rifa’atul Mahmudah (Journal of Health (JoH), 2025)
Complementary therapy is an alternative non-pharmacological treatment that can control blood pressure in hypertension sufferers. The apiin compound content in celery leaves and bay leaves is believed to be able to reduce high blood pressure. To determine the effectiveness of complementary therapy of boiled celery leaves and bay leaves on reducing hypertension. The research uses a quantitative approach with a Quasi Experiment One Group With Pretest-Posttest Design. The instruments in this research were observation sheets and aneroid spygmomanometer. The sample was 14 hypertensive patients in Paku Alam Village with a purposive sampling technique. Data analysis used the Wilcoxon test and data collection used observation sheets. From the results of Wilcoxon's statistical tests before and after the test, it can be concluded that the pre and post systolic and diastolic results of celery leaves achieved significant results.The effectiveness of complementary therapy of boiled celery leaves and bay leaves has an effect on reducing hypertension in the community in Paku Alam Village.The results showed that after giving a decoction of celery leaves and bay leaves, the blood pressure of respondents decreased. Wilcoxon's test results showed that bay leaf intake was more effective in reducing high blood pressure, there was a significant difference after giving bay leaf decoction.